(untitled) (International Journal of Engineering and Computer Science, 2014)
In Cloud, data are stored on servers at a remote location. Cloud computing provides the resources to the bussiness customers based on their needs. In cloud computing, Resource Allocation (RA) is the process of assigning available resources to the needed cloud applications over the internet.The Cloud providers deliver application via the Internet, which are accessed from web browser. Resource allocation starves services if the allocation is not managed precisely. Resource Allocation Strategy (RAS) is all about integrating cloud provider activities for utilizing and allocating scarce resources within the limit of cloud environment so as to meet the needs of the cloud application. By using virtualization technology the resource multiplexing is done in the cloud environment.To allocate the data center resources dynamically,we present a system that uses virtualization technology.And minimizing the number of servers used,we can support the green computing.And to measure the unevenness in the multidimensional resource utilization of a server we introduce the skewness concept. By minimizing skewness, we can improve the overall utilization of server resources. To prevent the overload in the system effectively while saving energy used, We develop a set of heuristics.